Insights into Nuclear G-Protein-Coupled Receptors as Therapeutic Targets in Non-Communicable Diseases - Salomé Gonçalves-Monteiro; Rita Ribeiro-Oliveira; Maria Sofia Vieira-Rocha; Martin Vojtek; Joana B. Sousa; Carmen Diniz (MDPI AG, 2021)
G-protein-coupled receptors (GPCRs) comprise a large protein superfamily divided into six classes, rhodopsin-like (A), secretin receptor family (B), metabotropic glutamate (C), fungal mating pheromone receptors (D), cyclic AMP receptors (E) and frizzled (F). Until recently, GPCRs signaling was thought to emanate exclusively from the plasma membrane as a response to extracellular stimuli but several studies have challenged this view demonstrating that GPCRs can be present in intracellular localizations, including in the nuclei. A renewed interest in GPCR receptors' superfamily emerged and intensive research occurred over recent decades, particularly regarding class A GPCRs, but some class B and C have also been explored. Nuclear GPCRs proved to be functional and capable of triggering identical and/or distinct signaling pathways associated with their counterparts on the cell surface bringing new insights into the relevance of nuclear GPCRs and highlighting the nucleus as an autonomous signaling organelle (triggered by GPCRs). Nuclear GPCRs are involved in physiological (namely cell proliferation, transcription, angiogenesis and survival) and disease processes (cancer, cardiovascular diseases, etc.). In this review we summarize emerging evidence on nuclear GPCRs expression/function (with some nuclear GPCRs evidencing atypical/disruptive signaling pathways) in non-communicable disease, thus, bringing nuclear GPCRs as targets to the forefront of debate.